2015
DOI: 10.5902/2179769211474
|View full text |Cite
|
Sign up to set email alerts
|

Laboratório de enfermagem: estratégias criativas de simulações como procedimento pedagógico

Abstract: RESUMO: Objetivo: relatar a experiência da utilização de iPads como ferramenta pedagógica e criativa em situações de simulação de aprendizagem no Laboratório de Cuidado Humano (LCH) do curso de Enfermagem. Método: relato de experiência da utilização de tecnologia da informação na simulação realística como estratégia pedagógica para ensino de procedimentos e cuidados de enfermagem. O projeto teve início no segundo semestre de 2012, com alunos da graduação de Enfermagem do quinto e sexto nível, o mesmo professor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 9 publications
0
4
0
6
Order By: Relevance
“…The insertion of technologies in the teaching-learning process has been promoting transformations in the teaching work, demanding new positions from this worker, such as greater creativity, easy adaptation to changes and selflearning [15][16] . In addition, technology promotes the invasion of the work space in the professional's private life, in which he feels obliged to be "connected" full time.…”
Section: Discussionmentioning
confidence: 99%
“…The insertion of technologies in the teaching-learning process has been promoting transformations in the teaching work, demanding new positions from this worker, such as greater creativity, easy adaptation to changes and selflearning [15][16] . In addition, technology promotes the invasion of the work space in the professional's private life, in which he feels obliged to be "connected" full time.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação à primeira categoria, o uso da simulação na prática do ensino da enfermagem, um estudo demonstrou que a simulação realística atualmente é a estratégia de ensino mais utilizada, por diversos motivos, desde garantir um ensino-aprendizado mais eficiente, motivador e interativo, pois oferecem aos estudantes maior facilidade para compreender o assunto estudado inclusive permite uma repetição do tema quantas vezes forem necessárias, respeitando o individualismo do aprendizado Figueiredo (2015).…”
Section: Discussionunclassified
“…As simulações de casos tem a grande vantagem de preparar os alunos para situaçõesproblema que serão encontradas na realidade assistencial (Figueiredo, 2015).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…The application provided several pertinent auscultation sounds to the clinical case in question. This allowed that students had a practice experience similar to reality, and the opportunity to improve their skills, thereby generating less exposure and risk to the patient because of students' inexperience (37) . In the same perspective, in study B (described in Chart 4), was demonstrated how the mVeinVision application helped Nursing students to improve their venipuncture technique by causing less harm to the patient (19) .…”
Section: Mobile Technologies In Nursing For Undergraduate Studentsmentioning
confidence: 99%